Strengthening Leadership and Islamic Work Ethics Through Employee Characteristics in Improving The Function of Risk Management in Bank SUMUT Syariah - Muhammad Fahmi; Azhari Akmal Tarigan; Sugianto Sugianto (Al-Intaj)
ABSTRACT